A review of the alignment between the Integrated Development Plan and the performance management system of Capricorn District Municipality - Khumalo, Ngwadeni Nompumelelo Yvonne (Stellenbosch : Stellenbosch University, 2015)
Thesis (MPA)--Stellenbosch University, 2015.